DAMPAK KEBIJAKAN PENGARUSUTAMAAN GENDER DALAM MENINGKATKAN KETAHANAN DIRI PEGAWAI PEREMPUAN. STUDI KASUS: PUSAT PELAPORAN DAN ANALISIS TRANSAKSI KEUANGAN - Fatimah; Samputra, Palupi Lindiasari (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2025)
This study examines the resilience of women in Indonesia’s Financial Transaction Reports and Analysis Center (INTRAC/PPATK) amid gender mainstreaming policies while managing dual roles as employees and mothers (double burden). Resilience is assessed through four components: Overcoming, Steering Through, Bouncing Back, and Reaching Out. Using a descriptive quantitative approach, a survey was conducted with 32 purposively selected respondents—female employees with children aged 0-7 years. Overcoming increased by Leave Flexibility and Work Environment (93.8% of respondents) and decreased by Workload (78% of respondents). Steering Through increased by Leave Flexibility and Work Environment (93.8% of respondents) but were hindered by Workload (78% of respondents). Bouncing Back improved with Office Facilities and Work Environment (96.9% of respondents) and Leave Flexibility (87.6% of respondents). Reaching Out benefited from Leave flexibility and the work environment (96.9% of respondents) and flexible working hours (78.1%) but declined due to workload (78.1% of respondents). Office facilities also contributed to overcoming, steering through, and reaching out. Key challenges included children’s health and development, workload, finances, and childcare. Additional obstacles were time management, childcare, workload, and maternal health. Strategies to cope involved collaboration, communication, quality time with children, effective time management, and enhancing emotional and spiritual intelligence.